Water mites of the genus Lebertia Neuman (Acari: Hydrachnidia: Lebertiidae) from China, with description of three new species - Wang, Yu; Jin, Daochao; Guo, Jianjun (Zootaxa, 2024)
Three new water mite species of the genus Lebertia Neuman, 1880—Lebertia (Lebertia) gimina sp. nov., Lebertia (Mixolebertia) dinghuensis sp. nov. and Lebertia (Mixolebertia) wuyiensis sp. nov.—are described from China, along with one new Chinese record—Lebertia (Lebertia) ignatowi Sokolow, 1930. The key characteristics for the subgenera of Lebertia are given.